Upaya perbaikaan gizi remaja melalui penerapan empat pilar gizi seimbang dan pengenalan jajanan tradisonal - Azzahra, Fatimah (Maliki Interdisciplinary Journal, 2024)
A country is said to have a developed nation based on the level of health, intelligence, and productivity at work, these three things are influenced by the state of nutrition. In the current era of globalisation, Indonesia is faced with multiple nutrition problems, this occurs due to changes in lifestyle and diet, especially among adolescents. Based on these problems in this study it is necessary to make efforts to improve nutrition problems among adolescents. The research method used in this research is descriptive qualitative. This study uses total sampling with the number of samples used as many as 50 respondents, data collection is done online using google form. Based on data collection, it was found that adolescents pay less attention to the limits of GGL consumption, less hygiene before and after eating, less in monitoring their body weight to remain ideal and lack of physical activity can increase the risk of obesity. Teenagers also prefer snacks such as snacks even though most snacks are empty of calories, besides that they also contain very few nutrients. This is a factor in nutritional problems in adolescents. Efforts that can be made in overcoming these nutritional problems can be through the application of the 4 pillars of balanced nutrition and by preserving nutritious traditional snacks are expected to improve nutritional status and can preserve Indonesian culture which has begun to fade with the times.